Tydeid mites on persimmons - Tomkins, A.R; Wilson, D.J.; Thomson, C.; Allison, P. (New Zealand Plant Protection, 2000)
Tydeid mites (Orthotydeus californicus and O caudatus) occasionally contaminate persimmon fruit Their abundance and phenology on fruit from persimmon (Diospyros kaki) trees in Whangarei Pukekohe Morrinsville Bay of Plenty and Gisborne was investigated over three seasons (1995/96 1996/97 and 1997/98) Few mites were found on fruit from all districts except Bay of Plenty and Gisborne Fruit contamination began in December peaked in February declined from March or April and varied considerably between seasons Mite abundance on persimmon trees was not related to their proximity to poplar shelter trees a suspected source of the mites